“Não estamos em crise, estamos em Cristo !” : como a representação evangélica se fortaleceu em meio à crise brasileira - Sávio Silva de Oliveira (2024)
This work examines the dynamic interaction between the Brazilian crisis and the strengthening of evangelical representation in the country. The objective is to understand how these phenomena coexist and influence each other in the sociopolitical context of recent years. The research adopts a case study, focusing on a specific phenomenon (the strengthening of evangelical representation) within a particular context (the Brazilian crisis). To achieve this, an interpretive qualitative approach is used, seeking to explore a comprehensive panorama and produce an in-depth analysis. The analysis was conducted through thematic axes defined from a Systematic Literature Review (SLR). Four main axes stood out: evangelical theological interpretations, political behavior in times of crisis, fragility of the party system and strategic partnerships in the Legislature. These axes form a comprehensive explanation of how evangelical representation was strengthened in the midst of the Brazilian crisis, which I describe didactically as follows: values ​​that become preferences → preferences that create demands → demands that become mandates wanting more space → conquered space that is consolidated with partnerships. Each of these interconnected processes depends on the multifaceted context of the Brazilian crisis, as well as the uncertainty and chaos of the unpredictable times of postmodernity, which makes religious fundamentalism an attractive alternative for many people to deal with losses. Especially in such an unequal country, where faith in the Sacred is the only consolation in times of pain.